Expansion of Higher Education: Realities and meanings in some Portuguese and Spanish speaking countries (Revista Lusófona de Educação, 2024)
In recent decades; there has been an expansion of higher education (HE) in most countries, resulting in anincrease in the number of institutions, courses and students, but also in the diversification of the profiles of these new entrants. In this article, we intend to describe the organization and process of access to HE in some Portuguese or Spanish-speaking countries (Angola, Brazil, Costa Rica, Spain, Mozambique and Portugal), pointing out the legislation and practices that support its expansion. In particular, the policies that have increased the heterogeneity of the student population are highlighted, favoring equal access opportunities for students from more disadvantaged sociocultural groups. Conclusions point to the existence of very different higher education structures in these countries.At the same time, there is a growing concern with the implementation of access measures for different audiences adapted to the cultural specificities of each country, leaving in HEIs the responsibility to implement measures that favor the adaptation and success of students who enter with different profiles from more traditional students.Keywords: higher education; expansion of higher education; access to higher education; democratization of higher education.